EXPRESSION OF DIALOGUE BETWEEN CHILD AND ADULT IN PRE-SCHOOL: THEORETICAL ASPECT - Vietienė, Inesa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
As economic, social and political conditions are rapidly changing and information and communication technologies are constantly developing, the approach towards the child and his education in childhood is changing in a modern society too. Child education is based on the mutual dialogue between child and adult which is often interpreted in the context of communication theory by addressing the question on the ways and forms of conveying information as well as by searching for the possibilities of correct and effective communication. A deeper understanding of dialogue expression is supplemented and enriched by the hermeneutic approach by the author which enables one to interpret the diversity of child and adult as well as learner and educator experiences. Hermeneutics provides conditions for child education to be perceived in a formal environment, i.e. pre-school, as a multi-dimensional and unique process. From the hermeneutic perspective, the dialogue between child and adult is oriented towards the problem of understanding where the understanding of the whole by interpreting personal experience and its perception rather than participation and interaction is of particular importance.